Pengaruh Pembelajaran Kurikulum Berbasis Kompetensi Pada Mata Kuliah Jaringan Komputer (Studi Kasus : Program Studi Teknik Informatika-Universitas Semarang) - Sri Handayani (Jurnal Transformatika, 2017)
The even semester 2014/2015 Technical Information Engineering University of Semarang (USM) has been running the Competency Based Curriculum (CBC) in the management of learning. Conversions that occur in some subjects at an increase in scheduled meetings in the classroom or in the laboratory. Computer Networks is one of the subjects who experienced a conversion. In the curriculum in 2008, Computer Networking has a number of credits 3. From the 2 credits 3 credits are for credits 1 credits for theory and practical credits. While at the CBC in 2013, Computer Networking has 4 credits, with details of 2 credits 2 credits theory and practicum. As lecture and instructor Computer Network, researchers interested in studying the effect of applying the CBC in 2013 in the subje ct of Computer Network. Does the addition of meeting practical and theoretical material renewal in accordance with the expected competencies?. Researchers tried applying the CBC in 2013 by conducting action research. Implementation of the research was conducted during an ongoing lecture that even semester 2015/2016. The results of the study during the first half of researchers will compare with the achievements that never existed when the old curriculum still in use. The goals of this research is, subjects in the Computer Network has always been one of the subjects that the content of the material and its application in the lab was able to follow the needs of the workforce